Biology of advanced uveal melanoma and next steps for clinical therapeutics. (1st September 2014) - Luke, Jason J.; Triozzi, Pierre L.; McKenna, Kyle C.; Van Meir, Erwin G.; Gershenwald, Jeffrey E.; Bastian, Boris C.; Gutkind, J. Silvio; Bowcock, Anne M.; Streicher, Howard Z.; Patel, Poulam M.; Sato, Takami; Sossman, Jeffery A.; et al.
Summary Uveal melanoma is the most common intraocular malignancy although it is a rare subset of all melanomas. Uveal melanoma has distinct biology relative to cutaneous melanoma, with widely divergent patient outcomes. Patients diagnosed with a primary uveal melanoma can be stratified for risk of metastasis by cytogenetics or gene expression profiling, with approximately half of patients developing metastatic disease, predominately hepatic in location, over a 15‐yr period. Historically, no systemic therapy has been associated with a clear clinical benefit for patients with advanced disease, and median survival remains poor. Here, as a joint effort between the Melanoma Research Foundation's ocular melanoma initiative, CURE OM and the National Cancer Institute, the current understanding of the molecular and immunobiology of uveal melanoma is reviewed, and on‐going laboratory research into the disease is highlighted. Finally, recent investigations relevant to clinical management via targeted and immunotherpies are reviewed, and next steps in the development of clinical therapeutics are discussed.